Socio-cultural Effects on Knowledge Sharing in Collaborative Co-located Software Engineering - Huynh, Anders; Lam, Danny (My University, 2021)
Context: Software engineering is an activity involving tedious and time-consuming processes. It is a social activity that requires collaboration between many different developers. Due to the collaboration between different developers, there is a risk of social barriers that can impact the quantity and quality of shared knowledge. The most common challenges that many developers face are generally related to cultural diversities and lack of cultural awareness. Objective: The purpose of this study is to investigate how socio-cultural difference influences knowledge sharing in co-located collaborative software engineering. In addition, identifying challenges that occur due to the influence of socio-culture. Methods: An extensive literature review is conducted by searching in established scientific databases in order to identify and gather knowledge about socio-cultural challenges associated with software engineering. In addition, understanding the concept and the problems regarding culture and software engineering and how it affects knowledge sharing. An interview form, together with a questionnaire, was created based on the findings from the literature review. Interviews are conducted across multicultural software development organizations located in Sweden to learn about the issues software development teams face regarding culture, how these teams face it as well as help give a more extensive knowledge of their adaption to it. A total of 10 interviews were conducted to investigate challenges related to socio-cultural and how it impacts knowledge sharing. Literature evidences were utilized to support the results collected from interviews. Results: Together with a complementary questionnaire, the interviews identified four factors that hamper effective communication and knowledge sharing. The impact of seniority and the impact of hierarchy resulted in consequences such as the unwillingness to express disagreement and opinions openly. The impact of language barriers and cultural behaviour may cause misunderstandings and misinterpretations of communication and shared knowledge. Conclusion: The study signifies the importance of understanding how socio-cultural aspects influence knowledge sharing between members in co-located teams, which also gives a different perspective to existing research. The study draws insights into various non-technical factors such as cultural, human, organizational, and social while collaborating in a co-located environment. Variations across these factors will lead to issues in regards to mutual understanding, collaboration, and communication.
Keywords: Knowledge sharing; culture; collaboration; socio-culture; co-located; software engineering